Effect of black cumin seeds on growth performance, nutrient utilization, immunity, gut health and nitrogen excretion in broiler chickens. (6th March 2017) - Kumar, Pawan; Patra, Amlan Kumar; Mandal, Guru Prasad; Samanta, Indranil; Pradhan, Saktipada
Abstract: BACKGROUND: Use of antibiotic growth promoters (AB) as feed additives in broiler chickens poses risks due to cross‐resistance amongst pathogens and residues in tissues. The aim of this study was to evaluate the effect of dietary supplementation of black cumin seeds (BCS) as a natural growth promoter in chickens on nutrient utilization, intestinal microbiota and morphology, immunity, antioxidant status, protein deposition in muscles and nitrogen excretion. RESULTS: Broiler chickens were fed BCS at 0, 5, 10 and 20 g kg −1 diet. Body weight gain tended to increase ( P = 0.10) and daily feed intake increased quadratically with increasing concentrations of BCS in the diets. Supplementation of BCS resulted in a tendency to decrease feed conversion efficiency on days 28–42. Metabolizability of nutrients increased linearly with increasing doses of BCS. Protein deposition in thigh and breast muscles was increased and nitrogen excretion was reduced by BCS and AB compared with the control (CON). Intestinal morphology in the duodenum, jejunum and ileum was not generally affected by BCS. Counts of total bacteria, Escherichia coli, Lactobacillus spp. and Clostridium spp. were not affected by BCS and AB compared with CON, but Salmonella spp. decreased linearly ( P = 0.05) with increasing doses of BCS. Antibody titers against Newcastle disease virus on day 35 increased quadratically ( P < 0.001) with increasing doses of BCS. Concentrations of glucose and triglyceride in blood were not affected by BCS. Concentrations of cholesterol decreased linearly while the concentration of total protein increased linearly with increasing doses of BCS. CONCLUSION: The use of dietary BCS may improve growth performance, immunity and nutrient utilization in broiler chickens. © 2017 Society of Chemical Industry